Bem-estar animal no manejo pré-abate e abate de aves: revisão de literatura - Albuquerque, Mariana Silva (2019)
Animal Welfare is characterized by ensuring adequate management conditions, whether it is the nutritional, environmental or genetic parameters, making it possible to animal adapt and interact in the best possible way to the environment in which it lives. Thus, this study aims to conduct a bibliographic review on animal welfare in pre-slaughter and slaughter management of chicken, describing pre-slaughter activities, stunning, bleeding and the Certified Humane® program. Improper handling of animals during pre-slaughter and slaughter can represent significant losses in meat quality and value, also being a key factor in ensuring welfare in poultry production. To this end, the particularities of each species must be respected from catching the animals at the farm until the time of slaughter, therefore, avoiding animal maltreatment and to promote actions aimed at animal protection and welfare. Once welfare standards are met, the chances are high that a quality end product will be obtained without high levels of partial or total carcass condemnation.